INSTAGRAM MANAGEMENT STRATEGY TO INCREASE NEW STUDENT ENROLLMENT: A CASE STUDY OF SDIT AL-HIKMAH (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the Instagram social media management strategy in increasing the number of new student enrollments at SDIT Al-Hikmah. This research employed a qualitative approach using a case study method. The data sources consisted of primary data obtained through interviews and observations, as well as secondary data in the form of documentation related to the school's social media management. The study was conducted at SDIT Al-Hikmah in 2025. The research informants included the principal, social media administrators, and other relevant parties selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, while data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the Instagram management strategy has included content planning, content publication, audience interaction, and account performance evaluation. However, its implementation has not been optimal due to the lack of structured content planning, inconsistent posting schedules, underutilization of Instagram features, and limited human resources. These conditions have reduced the effectiveness of Instagram in reaching the public and attracting prospective students. The study concludes that social media management should be strengthened through the development of a content calendar, optimization of interactive features, improvement of visual content quality, utilization of analytics, and enhancement of two-way communication to improve the school's image, expand information reach, and sustainably increase new student enrollment.